Investigation into the determinants of decision speed in product elimination decision (decision-reaching and implementation) processes in cosmetic industries - Homa Doroudi; Yasser Heidari (تصمیم گیری و تحقیق در عملیات)
Purpose: One of the issues faced by the managers of production and commercial organizations, which generally requires making challenging decisions with high risk and fast, is removing the product. Removal of a product for various reasons such as its life cycle status, entry of similar products and loss of market, lack of technical and economic justification for continuing its production and supply or the decision to enter newer products, product diversity, competition, activities of companies in the innovative environment. The weakness of the product is placed on the agenda of an organization. This research aims to "investigate the factors that determine the decision-making speed in the process (adoption and implementation) of the decision to remove the product in the cosmetics industry.Methodology: This was applied research using a descriptive-analytical design, and a survey method; the study was causal in nature. The questionnaire validity using validity and factorAnalysis and reliability was approved by reported of total Cronbach's alpha coefficient (0/834). The study population included the managers and administrators of Zarrin Cellulose Saveh Company in 2016. Suitable descriptive and inferential statistics, and SPSS and PLS, were used for data analysis.Findings:  The findings suggest that structural-temporal characteristics, decision-specific factors and environmental have a significant effect on the speed of Product Elimination Decision-Making (PEDM) process. The PEDM decentralization at the tactical level, centralization of PEDM power, polychronicity, and environmental turbulence have a positive and significant effect on the speed of PEDM process. The polychronicity reinforces the positive effect of decentralization at the tactical level on the speed of PEDM process. The product significance in the company's image and history and environmental complexity has a negative and significant effect on its speed. The speed of PE decision process for products in their birth and growth stage is more than those in their maturity and decline stage. The environmental complexity weakens the positive effect of polychronicity on the speed of PEDM process. Environmental turbulence weakens the negative effect of environmental complexity on the PE decision-reaching speed, but has no effects on the PE implementation speed.Originality/Value: The output of this research is to determine the effective factors in the speed of decision-making in the process (adoption and implementation) of the product removal decision in the cosmetics industry.